Die weißen Herren von Broda : Klosternachbarn des 750jährigen Neubrandenburg - Kienscherf, Dietrich (Schweriner Volkszeitung : unabhängige Tageszeitung für das Land Mecklenburg-Vorpommern, 1997)
Keywords: broda

Santa Maria d'Arta, Santa Maria de Bellpuig, Santa Maria de Sant Salvador - Llorenç Lliteras, Lorenzo (Revista Bellpuig, 1997)
Keywords: bellpuig de artá

Katalog prepozytów klasztoru norbertanek w Strzelnie od XII wieku do 1837 r. - Kabaciński, Ryszard; Karczewski, Dariusz (Nasza Przeszłość, 1997)
The Norbertine monastery in Strzelno was founded by Piotr Wszeborowic, the voivode of Kuyavia and the castellan of Kruszwica, in the late 1280s. Organizationally, it was subordinated to the monastery of Saint Vincent in Wrocław. The first mention of provosts appears in sources only in 1220. The provosts came to Strzelno mainly from the monastery in Wrocław, but not all of them came from Silesia. With the election of Gregory of Milejów, the period of provosts coming from Polish monasteries, mainly from the middle class, begins. Only in the 16th century did representatives of the nobility appear. From the 14th to the second half of the 16th century, the office of provost in Strzelno was often a step towards promotion to the position of abbot of the monastery in Wrocław. The vast majority of monasteries of the Polish Premonstratensian Circaria did not keep catalogs of their abbots or provosts, which would constitute a valuable source of information about the internal life and traditions of these monasteries. The exception is the chronicle of the abbots of the monastery of St. Vincent in Wrocław, written down by Prior Mikołaj Liebental by 1504 and continued until 1692. In the Norbertine monastery in Strzelno, as in other houses of this rule, the list of local provosts was compiled only in the first decades of the 18th century. This list was made on a blank page of the monastery copier from around 1573. The list of provosts was compiled on the basis of monastic documents and archival materials, as well as the historical memory of the successors in the position of provost. It is therefore necessary to develop a complete catalog of the superiors of the provostship in Strzelno, which would facilitate knowledge of the history of this monastery and contribute to more detailed research on the clergy, especially the monastic clergy. The chronological framework of this catalog is determined by the first mentions of the superiors of the Norbertine monastery in Strzelno and the year 1837, when the monastery was finally liquidated by the Prussian authorities.
Keywords: strzelno

Beauport, une abbaye de Prémontrés en Goëlo: aménagement d'un espace côtier du XIIIe au XVe siècle - Attal, François (La TILV, 1997)
Keywords: beauport

Aus der Geschichte der Wüstung "Kloster Barthe", Landkreis Leer, Ostfriesland: Ergebnisse der archäologischen Untersuchungen in den Jahren 1988 bis 1992 - Bärenfänger, Rolf; Burkhardt, Angelika; Löhnertz, Werner; Weßels, Paul (Probleme der Küstenforschung im südlichen Nordseegebiet, 1997)
Keywords: barthe

Burggraf und Ordensgründer: Gottfried von Cappenberg: vor 900 Jahren wurde der Stifter des Prämonstratenserklosters Cappenberg bei Lünen geboren - Beaugrand, Günter (Unser Westfalen. Jahrbuch, 1997)
Keywords: cappenberg

Die ehemalige Prämonstratenser Klosterkirche St. Maria und Michael in Churwalden: Kanton Graubünden - Bergmann, Uta (Schweizerische Kunstführer, 1997)
Keywords: churwalden

Quand l'abbé Pierre réglementait la pitance à l'abbaye de Beauport - Bernard, Michel-Yves; Lejeune, Anne (Les Prémontrés et la table : actes officiels du 22e Colloque du Centre d'études et de recherches prémontrées, Prémontré, Laon, 11-13 octobre 1996, 1997)
Keywords: beauport

Dona dantes et vota voventes. De stichting en dotatie van het norbertijnenklooster te Postel (1128/1138-1179) - Bijsterveld, Arnoud-Jan A. (Analecta Praemonstratensia, 1997)
Keywords: postel

Ügyintézési törekvések a leleszi hiteleshelyen a XIV. és XV. század fordulóján - Borsa, Iván (Miscellanea fontium historiae Europae: Emlékkönyv H. Balázs Éva történészprofesszor 80. születésnapjára., 1997)
Administration of the place of authentication in Leles at the turn of the 14th-15th centuries
Keywords: leles

The Floreffe Bible frontispiece (London, B.L. add. ms. 17738, fol. 3v-4r) and twelfth-century contemplative theory - Bouché, Anne-Marie (Columbia University, 1997)
Keywords: floreffe

Arthous, une abbaye prémontrée - Bouchon, Olivia (Université de Pau et des Pays de l'Adour, 1997)
Keywords: arthous

Autour des anciennes orgues de l'abbaye prémontrée de Blanchelande - Bouvris, Jean-Michel (Bulletin de la Société des Antiquaires de Normandie, 1997)
Keywords: blanchelande

Schätze aus alten Klosterbibliotheken in Oelinghausen: das geistliche Leben westfälischer Prämonstratenser im Spiegel ihrer Bibliotheken - Brockmann, Daniela (Sauerland, 1997)
Keywords: oelinghausen

Le temporel de l'abbaye Notre-Dame de Fontcaude: milieu XIIe-XIIIe siècles: histoire de la prospérité d'une seigneurie ecclésiastique face à son siècle - Canovas, Guillaume (University of Montpellier, 1997)
Keywords: fontcaude

K nejstaršímu raně středověkému osídlení bývalého Kláštera Hradisko u Olomouce - Cižmár, Zdenek; Kohoutek, Jirí (Z pravěku do středověku : sborník k 70. narozeninám Vladimíra Nekudy, 1997)
[Zur ältesten frühmittelalterlichen Besiedlung des Klosters Hradisko bei Olmütz]
Keywords: hradisko

Santa María de Bellpuig de les Avellanes : páginas de historia catalana - Corredera Gutiérrez, Eduardo (Institut de Germans Maristes-Catalunya D.L., 1997)
Keywords: bellpuig de las avellanes

Die Gelnhäuser Schenkung Gotberts an Kloster Meerholz im Jahre 1190. Zum Textfund einer Urkunde König Heinrichs VI. - Decker, Klaus Peter (Hessisches Jahrbuch für Landesgeschichte, 1997)
Keywords: meerholz

Kloster und Domäne Konradsdorf - Decker, Klaus Peter (Der Vogelsberg, 1997)
Keywords: konradsdorf

De abt van Middelburg: ambachtsheer, dijkgraaf en prelaat - Dekker, Cornelis (Norbertijnen in de politiek, 1997)
Keywords: middelburg

De stichting van de abdij van Averbode en het klooster Keizerbos in het graafschap Loon - Dekkers, Peter J.V. (De Maasgouw, 1997)
Keywords: averbode; keizerbosch

Les ressources en poissons de l'abbaye de La Lucerne (Manche) aux XIIe et XIIIe siècles - Ducoeur, Danièle (Les Prémontrés et la table : actes officiels du 22e Colloque du Centre d'études et de recherches prémontrées, Prémontré, Laon: 11-13 octobre 1996, 1997)
Keywords: la lucerne

Sainte-Anne d'Ares et Girosp: deux fondations de Prémontrés en Comminges - Ducos, Jacques (Chemins de découverte, 1997)
Keywords: sainte-anne-des-arres

Zur Besitz- und Wirtschaftsgeschichte des Klosters Wirberg im Spätmittelalter (13. bis frühes 16. Jahrhundert) - Eckhardt, Albrecht (Hundert Jahre Historische Kommission für Hessen, 1997)
Keywords: wirberg

Neue Ausgrabungen im Prämonstratenserkloster Windberg, Lkr. Straubing-Bogen - Ernst, Bernhard (Vorträge des 15. Niederbayerischen Archäologentages, 1997)
Keywords: windberg

Een archeologische waarneming in het Oldenklooster, Kloosterburen (gem. De Marne) - Essink, M.; Schoneveld, J. (DANS Data Station Archaeology, 1997)
Keywords: marne (oldeklooster)

Das Kloster Dorlar wurde als Bildungsstätte für die Töchter vermögender Bürgerlicher gegründet: im Jahr 1297 begründete Eberhard von Merenberg das Nonnenkloster - Großteil der Anlage abgerissen - Ewert, Franz (Heimat im Bild. Beilage des Gießener Anzeiger, 1997)
Keywords: dorlar

El Monasterio de Santa María de las Dueñas "El Real" de la villa de Medina del Campo, también llamado de "Santa María de los Huertos" en la Baja Edad Media - Fernández Baizán, María Luz (150 aniversario del Instituto Padre Isla, 1997)
Keywords: medina del campo (santa maria)

Étude de l'évolution du bâtiment principal de l'abbaye Notre-Dame de Lieu-Restauré (Oise) du XIIIe au XVIIIe siècle - François, Jean-Luc (Revue archéologique de Picardie, 1997)
Gegründet im Jahre 1131 bei den Prémontrés, an der Stelle einer alte Kapelle, dadurch seine Name Locus Restauratus. Die erste Abtei, von romanischen Stil würde nah von dem klassischen cistercienser Stil schon gebaut. Das Hauptgebäude enthaltete die Sakristei, das Kapitelsaal, ein Gang, die Schreibstube und einen zusätzlichen Raum. Der Schlafsaal lag am ersten Stock. Östlich gab es ein Krankenzimmer. Im Laufen des XIII. Jahrhundert die Mönchen haben ein grosser Teil des Abtei neu gebaut auf Grund des sumpfiges Boden. Das neue Hauptgebäude ist langer als sein Vorgänger und einen senkrechten Flügel mit Abort würde gebaut, da wo das Krankenzimmer war. Die Abtei würde zerstört während des Hundertjahre Krieg, ca um 1430. Während das XV. und XVI. Jahrhundert, nur die Kirche und das Hauptgebäude würden mit alien neu groupierten Fonktionnen wiederaufgebaut. ; Die religiose Kriege im XVI. Jahrhundert und die Kommende im XVII. Jahrhundert haben die Abtei verarmt, aber ca im Jahre 1700 die Mönchen bauen ein neues Hautgebäude auf im klassichen Stil mit einem neuen Kloster und ein Gasthaus, die Kirche würde nicht modifiziert. Nach der französischen Revolution, die Abtei ist zerstört, während des XIX. Jahrhundert und die Kirche war ein Werk und dann einen Bauernhof geworden. ; Seit 1964, ein Verein mit freiwilligen Mitglieder versucht mit viel Mühe dieser Abtei zu retten.
Keywords: lieu-restauré

Kleiner Historischer Atlas des Stiftes Steingaden. Die Herrschaftsbesitzungen in Altbayern und Schwaben - Fried, Pankraz (Das ehemalige Prämonstratenserstift Steingaden, 1997)
Keywords: steingaden

Der "Dom" der Wetterau. Die ehemalige Prämonstratenserkirche in Ilbenstadt - Gärtner, Otto (Hessische Heimat. Aus Natur und Geschichte (Beilage der Gießener Allgemeinen), 1997)
Keywords: ilbenstadt

Zur Geschichte der Kloster- und Wallfahrtsstätte Beselich - Graulich, Markus (Beselicher Schriften: Informationen d. Vereins zur Erhaltung d. Klosterruine Beselich, 1997)
Keywords: beselich

Die barockisierte und die romanische Stiftskirche in Steingaden - Haas, Walter (Das ehemalige Prämonstratenserstift Steingaden, 1997)
Keywords: steingaden

Katholische Propsteikirche St. Walburga Werl - Hanewinkel, Heinrich (Schnell & Steiner, 1997)
Keywords: werl

Das sogenannte Necrologium aus Steingaden - Hauke, Hermann (Das ehemalige Prämonstratenserstift Steingaden, 1997)
Keywords: steingaden

Die Geschichte des Klosters Dorlar - Heider, Ernst (Lahnau in alten Bildern. Atzbach, Dorlar, Waldgirmes, 1997)
Keywords: dorlar

Notes sur deux manuscrits de la correspondance d'Yves de Chartres provenant de l'abbaye de Floreffe - Hermand, Xavier (Scriptorium, 1997)
Keywords: floreffe

Die Ergebnisse der archäologischen Ausgrabungen im Kloster Pernegg in den Jahren 1995 und 1996 - Hofer, Nikolaus (Geraser Hefte, 1997)
Keywords: pernegg

Heinrich von Bodwede, Albrecht der Bär und die Prämonstratenser. Aspekte und Perspektiven zur ersten Gründung des Klosters Ebstorf. Ein Entwurf - Homeyer, Joachim ("In Treue und Hingabe". 800 Jahre Kloster Ebstorf, 1997)
Keywords: ebstorf

Prämonstratenser - Horstkötter, Ludger (Kulturgeschichte der christlichen Orden in Einzeldarstellungen, 1997)
Keywords: 📚 premonstratensian (general)

Ut omnipotenti deo servire quietius valeant : das rechtliche und wirtschaftliche Beziehungsgeflecht schwäbischer Prämonstratensklöster im Hohen Mittelalter - Huber, Christoph (University of Tübingen, 1997)
Keywords: 🇩🇪 germany (general)

De praemonstratenzers van Grimbergen - Installé, Henri (Historische Stedenatlas van België Mechelen II, 1997)
Keywords: mechelen (grimbergen)

Bildstock birgt Rest des gotischen Sakramentshauses der Rheder St. Gudulakirche - Kamps, Markus (Westmünsterland, 1997)
Keywords: rhede

Kloster Broda war schon 75 Jahre früher da : vor dem 750jährigen Jubiläum Neubrandenburgs - Kienscherf, Dietrich (Anzeigenkurier: Neubrandenburg, Neustrelitz, Altentreptow, 1997)
Keywords: broda

Die Martinskirche in Zülpich - Koch, Wilfried Maria (Stadt Zülpich, 1997)
Keywords: zülpich

Dagboek van een opgraving in en om het klooster Houthem St. Gerlach - Krikke, Doeke (Doeke Krikke, 1997)
Keywords: sint-gerlach

K posloupnosti louckých opatů ve 13. století - Krmíčková, Helena (Časopis Matice moravské, 1997)
Zur Nachfolge der Äbte des Stiftes Klosterbruck im 13. Jahrhundert
Keywords: louka

Premonstrátský klášter v Louce - Kroupa, Petr; Kroupa, Jirí K.; Slavícek, Lubomír; Unger, Josef (Okresní úřad Znojmo, referát kultury ve spolupráci s Jihomoravským muzeem ve Znojmě, 1997)
Keywords: louka

Gemeente De Marne, Nieuwbouwplannen Kloosterburen. Waarderend archeologisch onderzoek - Langen, G.J. de; Perger, T.M. (1997)
Keywords: marne (oldeklooster)

Administratie en archief van het voormalig Nobertijnenklooster van Gempe ('s-Hertogenbosch) in Sint-Joris-Winge. Een lang en eeuwenoud verhaal - Lani, Stefan van (Analecta Praemonstratensia, 1997)
Keywords: gempe

Anselm of Havelberg: Deeds into Words in the Twelfth Century - Lees, Jay T. (Studies in the History of Christian Traditions, 1997)
Important for the political and literary history of the Middle Ages, Anselm served St. Norbert of Xanten, advised three German rulers, acted as a papal legate, and held the offices of bishop of Havelberg and archbishop of Ravenna. He is most famous for his written account of theological debates he held with a Greek archbishop and for his History of the Faithful. Lees's book is the first comprehensive study of Anselm's life and writings, drawing the two together in a new interpretation of the History, the Debates, and Anselm's blistering attack on the monastic life, as well. It will be of great value to those interested in medieval political, intellectual or church history, as well as those interested in the literature of the twelfth century.
Keywords: 👤 anselm of havelberg

"Alii nostrum...". Bischof Anselms Schilderung des Lebens in Havelberg - Lees, Jay Terry (Wichmann-Jahrbuch des Diözesangeschichtsvereins Berlin, 1997)
Keywords: 👤 anselm of havelberg

Zum Bildprogramm des Chorfensters in der ehemaligen Stiftskirche Elsey - Lingen, Helmut (Hohenlimburger Heimatblätter, 1997)
Keywords: elsey

Le rôle des méthodes de laboratoire dans le recherche de la provenance de dinanderies médiévales. Application aux fonts baptismaux de Tirlemont, aux chandeliers des abbayes de Postel et de Parc des Musées Royaux d'Art et d'Histoire de Bruxelles et aux fonts baptismaux de Saint-Barthélemy à Liège - Martinot, L. (Académie royale de Belgique: Bulletin de la classe des beaux-arts, 1997)
Keywords: park

Latin et langue vulgaire dans les chartes de Bellelay au XIVe siècle - Marzys, Zygmunt; Scheurer, Rémy (Nomen latinum: mélanges de langue, de littérature et de civilisation latines offerts au professeur André Schneider á l'occasion de son départ à la retraite, 1997)
Keywords: bellelay

Oelinghausen: ein Blick in die Geschichte des Kirchturms - Michel, Hubert (An Möhne, Röhr und Ruhr, 1997)
Keywords: oelinghausen

Le Prieuré-Hôpital Saint-Jacques de Zubernoa - Michelena, Manuel (Hendaye et son histoire, 1997)
Keywords: subernoa

Verwehte Spuren des Musiklebens im Kloster Steingaden - Münster, Robert (Das ehemalige Prämonstratenserstift Steingaden, 1997)
Keywords: steingaden

Detailprospektion zur Aufsuchung des Prämonstratenserklosters Grobe im Bereich des Priesterkamps südlich von Usedom - Peschel, Gerald J. (Tradition und Fortschritt archäologischer Forschung in Greifswald, 1997)
Keywords: grobe

Kloster Maria Engelport: Grablege adeliger Familien - Pies, Norbert J. (Selbstverlag, 1997)
Keywords: engelport

"Quod divinabat Norbertus ..." Das Prämonstratenserstift Steingaden zwischen Ideal und Wirklichkeit - Pörnbacher, Hans (Das ehemalige Prämonstratenserstift Steingaden, 1997)
Keywords: steingaden

Steingaden, 1147-1997: Festschrift zur 850-Jahr-Feier - Pörnbacher, Hans (A.H. Konrad, 1997)
Keywords: steingaden

K výzkumu zaniklého kláštera v Louňovicích pod Blaníkem a příspěvek k datu jeho založení - Radoměrský, Pavel (Muzeum a současnost, 1997)

Brzesko i Zwierzyniec. Jeszcze o początkach dwu najstarszych klasztorów norbertańskich w Małopolsce - Rajman, Jerzy (Roczniki humanistyczne, 1997)
Keywords: brzesko; zwierzyniec

Windberg: Klosterbibliothek - Rupprecht, Simeon (Handbuch der historischen Buchbestände in Deutschland: Bayern, 1997)
Keywords: windberg

Monasterios medievales premonstratenses: reinos de Castilla y León - Sanz, Maria Teresa López de Guereño (Estudios de arte, 1997)
Keywords: 🇪🇸 spain (general)

Die Geschichtsschreibung des Prämonstratenserstiftes Steingaden - Schmid, Alois (Das ehemalige Prämonstratenserstift Steingaden, 1997)
Keywords: steingaden

Kloster Broda - Schmidt, Volker (Neubrandenburg : ein historischer Führer, 1997)
Keywords: broda

Średniowieczne naczynia ceramiczne z klasztoru norbertanek w Strzelnie - Sułkowska-Tuszyńska, Krystyna (Wydawnictwo Ar-Gos Mariusz Tuszyński, 1997)
Keywords: strzelno

Spätgotische Seidenstickerei aus dem Katharinenkloster - Tillmann, Elisabeth (Heimat Dortmund: Stadtgeschichte in Bildern und Berichten, 1997)
Keywords: dortmund

Paimpol – Abbaye de Beauport, salle au Duc - Tournier, Fanny (ADLFI. Archéologie de la France - Informations. une revue Gallia, 1997)
L’abbaye de Beauport, fondée en 1202 et concédée aux prémontrés de la Lucerne en Normandie, est implantée au nord du département des Côtes d’Armor, sur l’actuel territoire de la commune de Paimpol. Elle s’élève sur le littoral d’une anse abritée, au débouché de deux vallées parallèles. Le site, acquis en 1992 par le Conservatoire du littoral, présente une remarquable qualité, tant par la conservation des élévations que par l’homogénéité de leur construction et leur valeur artistique. En outre...
Keywords: beauport

Besluit van het Maria-Magdalenaklooster te Nijmegen om toe te treden tot de Orde van Prémontré, 1344 - Velden, Gregorius Maria van der (Analecta Praemonstratensia, 1997)
Keywords: nijmegen

Die selige Gertrud von Altenberg starb vor 700 Jahren - am 13. August 1297 - Volkmar, Werner (Heimat an Lahn und Dill, 1997)
Keywords: altenberg

Barthe – Zur Geschichte eines Klosters und der nachfolgenden Domäne auf der Grundlage der Schriftquellen. - Weßels, Paul (Beiträge zur Geschichte der ostfriesischen Geestortes Hesel, 1997)
Keywords: barthe

Adam of Dryburgh and the Augustinian tradition - Worthen, Jeremy Frederick (Revue des études augustiniennes, 1997)
Keywords: 👤 adam of dryburgh

Das Kloster Rüti als Überlebensversicherung - Wüst, Emil (Jahrheft des Verkehrsvereins Rüti-Tann, 1997)
Keywords: rüti